Global political economy - Cohn, Theodore H. 1940- (Boston Pearson Longman, 2012)
Praised for its authoritative coverage, Global Political Economy places the study of IPE in its broadest theoretical context. This text not only helps students understand the fundamentals of how the global economy works but also encourages them to use theory to more fully grasp the connections between key issue areas like trade and development. Written by a leading IPE scholar, Global Political Economy equally emphasizes theory and practice to provide a framework for analyzing current events and long-term developments in the global economy.
Multinational corporations and global production -- Definitions and terminology -- Why do firms become MNCs? -- The historical development of FDI -- MNC-host country relations : determinants and effects of FDI -- Host country policies toward MNCs -- MNC-home country relations -- A regime for FDI : what is to be regulated? -- Bilateral investment treaties -- United Nations -- Regional approaches : the EU and NAFTA -- The GATT/WTO to the OECD and back to the WTO -- Private actors -- International development. IPE perspectives and North-South relations -- Official development assistance -- The World Bank Group -- LDC development strategies -- Import substitution industrialization -- Socialist development strategies -- Export-led growth -- The revival of orthodox liberalism -- Another shift in development strategy? -- Foreign debt and financial crises : What is a debt crisis? The origins of the 1980s debt crisis -- The foreign debt regime -- Strategies to deal with the 1980s debt crisis -- Transition economies and foreign debt -- The IMF, the World Bank, and the debt crisis -- The 1990s Asian financial crisis -- The 2008 Global Financial Crisis -- Part IV. Concluding comments. Current trends in the global political economy : Globalization -- North-North relations -- North-South relations -- A final word on IPE theory and practice.
Keywords: International economic relations; International trade; International finance